Peningkatan presisi forehand drive tenis meja melalui latihan multiball - Mongsidi, Wolter; Zaenal Arwih, Muhammad; Rusli, Muhammad; Marsuna, Marsuna (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
This study aims to determine the improvement of table tennis forehand drives through multiball exercises. The research method used a pre-experimental design (non-design) in the form of a one-group pretest and posttest design. The research subjects were students of senior hight school 3 Konawe Selatan who were 15 to 18 years old. The subject's body weight varies depending on the characteristics of each individual. However, in this study, body weight was only the main focus if specific aspects related to forehand driveability existed. Height range 150 to 190 cm. So, the number of samples in this study was 20 students who fit the age and height criteria. The instrument used uses a forehand drive test for 30 seconds with a target. Data analysis used description analysis and analysis prerequisite test with data normality test, data homogeneity test, and using t-test. Based on the pretest average score of 19.90 and the posttest average score of 23.35, using a percentage increase of 17.34% using multiball exercises. The data analysis results show a significant increase in the accuracy of the table tennis forehand drive through multiball training. By improving the accuracy of the forehand drive, players can direct the ball more, leading to better scores in competition and encouraging the development of more innovative and creative training approaches in the sport through multiball training, enhancing technical and tactical skills in the game.